Microalgal cultivation in open and closed systems under a tropical climate: A life cycle comparison - Prado, Larissa de Oliveira [UNESP]; Bolzani, Hugo Renan [UNESP]; Souza, Hugo Henrique de Simone; Ruas, Graziele [UNESP]; da Silva, Gustavo Henrique Ribeiro [UNESP] (Elsevier, 2023)
Microalgae can grow in different cultivation media, including domestic sewage, and have been used in several applications, including as biofertilizer in agriculture. Since microalgae have a cellular mechanism capable of using solar energy to synthesize bio-based compounds, the geographical location and appropriate climate conditions, such as radiation intensity and high temperature, increase the productivity and performance of cultivation systems. However, there are still few studies on microalgal cultivation in tropical areas, mainly to recover nutrients from domestic sewage for agricultural reuse of the biomass generated as biofertilizers. Aiming to overcome this lack of studies and to identify more environmentally sustainable solutions, life cycle assessment (LCA) method was employed to evaluate the potential environmental impacts of these microalgae cultivation systems. In this context, the aim of this study was to compare the potential environmental impacts of two systems: i) a raceway pond and ii) a flat panel photobioreactor on a pilot scale. Both systems were designed for microalgae cultivation under tropical climate conditions using domestic sewage anaerobically treated. The results indicated that the microalgae cultivation scenario in raceway pond was the worst option for the assessed impact categories. Sensitivity analysis showed that electricity consumption had a large influence on environmental impact while the use of inoculum did not significantly influence. Thus, electricity consumption increased the environmental impacts in most of the evaluated categories, however, the tropical climate conditions favored a decrease in the use of this input, helping to reduce the environmental impacts of the studied systems.
Keywords: Cultivation system; Flat panel photobioreactor; Life cycle assessment; Microalgae; Raceway pond